PERLINDUNGAN HUKUM BAGI FRANCHISEE USAHA MIKRO, KECIL, DAN MENENGAH DALAM BISNIS FRANCHISE - Deby Wulandari, Anak Agung; Putra Atmadja, Ida Bagus; Sri Indrawati, Anak Agung (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
This paper entitled “Legal Protection for Micro, Small, and Medium Enterprises Franchisees in Business Franchise”. This paper uses normative methods. The establishment of the law No. 20 year 2008 on Micro, Small, and Medium Enterprises and Government Regulation No. 42 Year 2007 on Franchise is intended to provide certainty and fairness among businesses for micro, small, and medium enterprises as well as to regulate franchising. But related to the partnership with the pattern of the franchise or franchising, if either normatively assessed act about Micro, Small, and Medium Enterprises and Government Regulations about Franchising does not provide justice and legal protection for franchise development of the Micro, Small, and Medium Enterprises sector.
Keywords: Legal Protection, Micro Enterprises, Small Enterprises, Medium Enterprises, Agreement, Franchise.